2022
DOI: 10.1039/d2cc03494h
|View full text |Cite
|
Sign up to set email alerts
|

Solution-phase synthesis of the chalcogenide perovskite barium zirconium sulfide as colloidal nanomaterials

Abstract: Chalcogenide perovskites such as BaZrS3 have promising optoelectronic properties. Methods to produce these materials at low temperatures, especially in the solution phase, are currently scarce. We describe a solution-phase synthesis...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 29 publications
1
34
0
1
Order By: Relevance
“…We recently reported the synthesis of BaZrS 3 nanoparticles at 330 °C, 20 with similar results reported by Zilevu at al. 21 Such nanoparticles are yet to be processed into device-grade films. Turnley et al 22 reported the solution-based synthesis of BaZrS 3 via sulfurization of an organometallic Ba precursor and ZrH 2 at temperatures above 550 °C; however, continuous, dense films were not possible in this approach.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the synthesis of BaZrS 3 nanoparticles at 330 °C, 20 with similar results reported by Zilevu at al. 21 Such nanoparticles are yet to be processed into device-grade films. Turnley et al 22 reported the solution-based synthesis of BaZrS 3 via sulfurization of an organometallic Ba precursor and ZrH 2 at temperatures above 550 °C; however, continuous, dense films were not possible in this approach.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Nanoparticles of BaZrS 3 have also been synthesized at temperatures less than 350 °C, providing evidence that these materials can be solution-processed. [16,17] But it remains to be seen if these nanoparticles can be processed into large-grain thin films. Our group recently developed a direct-tofilm solution-processed route for BaMS 3 (M = Ti, Zr, Hf ) materials that utilizes heat treatment in a sulfur-containing atmosphere at modest temperatures from 500 to 575 °C.…”
mentioning
confidence: 99%
“…입자의 분산을 위해서는 유기 리간 TEM image of the nanoparticles. [36] c. Chemical formular of the nanoparticle synthesis with DBuDTC. [37] 이재욱, 양우석 태로 기판 위에 도포하는 것에 성공하였다 [38] .…”
Section: Iodine 촉매 활용 고체상 반응법unclassified